Harmonization of National and International Laws in Disclosing Transnational Drug Networks Involving Child Couriers Through Money Laundering - Yudi Bintoro; Riswadi Riswadi (Lembaga Pengembangan Kinerja Dosen, 2026)
Transnational drug crimes develop in the form of adaptive, organized networks that exploit vulnerable groups, including children, as couriers. Law enforcement practices in Indonesia are dominated by an actor-based approach that focuses on field perpetrators based on Law Number 35 of 2009, while the asset tracking and confiscation instruments in Law Number 8 of 2010 have not been systematically optimized. At the same time, the principle of the best interests of children in Law Number 11 of 2012 has not been consistently integrated into organized drug cases. This study aims to analyze the paradigm disharmony between the narcotics regime, the money laundering regime, and the child protection regime, and to formulate an integrative model for dismantling transnational drug networks involving children. The method employed normative legal research with a legislative, conceptual, and comparative approach to international instruments, such as the United Nations Convention against Transnational Organized Crime and the United Nations Convention against Illicit Traffic in Narcotic Drugs and Psychotropic Substances. The study's findings demonstrate that a misalignment in legal philosophies leads to the criminalization of child couriers and the failure to optimize financial dismantling strategies, allowing networks to persist despite the arrest of perpetrators. The proposed reconstruction emphasizes a shift toward a network-based approach, mandatory parallel financial investigations, and the recognition of children as victimized actors within the structure of organized crime.